Analysis of the pushing phase in Paralympic cross-country sit-skiers - Class LW10 - Gastaldi, L.; Mauro, S.; Pastorelli, S. (Journal of Advanced Research, 2016)
Paralympic Cross-Country sit-skiers use adaptive equipment, with a resulting gesture similar to double poling techniques adopted by able-bodied skiers. Despite the similarity, a specific attention on the gesture performed by sit-skiers is needed. The paper focuses on the sledge kinematic and on inertia effect of upper body motion which is translated in a propulsive effect in the early stage of the pushing cycle. In particular a group of 7 elite sit skiers of class LW10 were recorded with a video-based markerless motion capture technique during 1 km sprint Paralympic race. A biomechanical model, consisting of 7 anatomical points and 4 technical ones, is used to track the kinematics from video-images, then body segments, joints of interest and relative angles are evaluated. In this paper we focus on the biomechanics of the poling cycle, in particular prior to the onset of pole plant. The aim was to evaluate the contribution of the upper body to the early stage of the propulsive action. To this porpoise body inertial forces for each athlete are calculated using kinematic data, then normalized with respect to the athlete`s body mass. The results show that in LW10 sit-skiers an important sledge propulsion, prior to the onset of pole plant, is provided by the inertial effect, due to the upper body region (arms and forearms) motion.